Evaluation and identification of pinto bean (Phaseolus vulgaris L.) genotypes suitable for low Input farming systems based on stress tolerance indices - Adel Ghadiry; Parviz Rezvani Moghaddam; Abdolreza Bagheri; Reza Ghorbani; Alireza Beheshti (پژوهش‌های حبوبات ایران, 2017)
Introduction Legumes such as Pinto Bean (Phaseolus vulgaris L.), in addition to the value of food and proteins production, they are able to fix biological nitrogen and therefore, are desirable for planting in sustainable agricultural systems in order to strengthen and preserve soil fertility. Low input farming systems (LIFS), which are a part of sustainable agricultural systems was defined as a way to optimize the use of ecological inputs and to minimize the use of inputs such as chemical fertilizers and pesticides in every time and every place to reduce the cost of production, reduce pollution of groundwater and surface water, reduce of pesticide residues in food, reduce total risk in agriculture and an increase in short and long term profitability of agriculture. Evaluation and identification of the suitable cropping plant cultivars for planting in low-input agricultural systems has begun three decades ago, in the world. The aim of this study was to identify of pinto bean genotypes suitable for cultivation in low input crop management system and use them in breeding programs and the cultivar release process of this crop.